Development of an Intellectual Property and Research Incentive Information System at Polman Babel - Jayya Muhammad, Taqiy; Afriansyah, Riki; Dwisaputra, Indra (KHARISMA Tech, 2025)
Politeknik Manufaktur Negeri Bangka Belitung (Polman Babel) is a higher-education institution that supports research and community service activities through its P3KM unit. In practice, lecturers play an active role in producing scientific works and innovations, including submitting incentive requests and registering Intellectual Property Rights (IPR). However, the previously google form submission process created several issues such as verification delays, data errors, and difficulties in tracking submission status. This study aims to develop a web based Intellectual Property and Lecturer scientific work Incentive Information System. The development employed the Rapid Application Development (RAD) method. The main features of the system include IPR proposal submission, scientific work incentive proposal submission, and validation panels for reviewers and P3KM administrators. Black-box testing results showed that all system functionalities operated according to the defined scenarios